To Develop A Sense Of Patriotism And Personal Responsibility Among Students In Higher Education Institutions - Avazovich, Uzakov Akrom; o’g’li, Khurramov Mansur Musurmon (The journal of contemporary issues in business and government, 2021)
The articles about with the advent of the self-media era, there are increasing ways for college students to acquire various kinds of information and knowledge. At the same time, the change in ideology wills also uproar. Some negative information on networks and media will affect young student, especially in the aspect of patriotic ideologies. Therefore, the requirement of patriotism education has been proposed, and a varied path of patriotic education has been conducted by the higher educational institutions within the self-media environment. The research will shed light on the problem that how to facilitate current college students actively take actions to self-educate and spread patriotism in the self-media environment.